The Influence of Liquidity, Solvency and Company Growth on the Provision of Going Concern Audit Opinion (Study on Transportation and Logistics Companies in 2021-2023 Listed on the Indonesia Stock Exchange) - Qinthara, Dhina Rizka; Nariman, Augustpaosa (Eduvest - Journal of Universal Studies, 2025)
In today's dynamic business environment, the ability of a company to continue its operations or maintain a going concern status is crucial, especially in capital-intensive sectors such as transportation and logistics. This study aims to examine the effect of liquidity, solvency, and company growth on the provision of going concern audit opinions in transportation and logistics companies listed on the Indonesia Stock Exchange for the 2021–2023 period. This quantitative research involved 101 companies as the population, with a sample of 75 companies selected using purposive sampling based on specific criteria. Data were analyzed using multiple regression techniques to test the significance of each independent variable. The results reveal that both liquidity and solvency have a positive and significant effect on the issuance of going concern audit opinions, indicating that higher liquidity and lower debt levels increase the likelihood of receiving a favorable opinion. In contrast, company growth was found to have no significant effect on the auditor’s decision to issue a going concern opinion. Additionally, the three variables simultaneously exert a significant influence on the provision of going concern opinions. These findings suggest that financial indicators related to short-term capability and capital structure are more influential in auditors’ assessments than growth metrics. The study implies the need for companies to maintain healthy liquidity and solvency levels to strengthen stakeholders’ confidence and sustain their operational continuity. Future research is recommended to include qualitative factors or external economic conditions that may affect auditors’ judgments.